New and old buildings microenvironment – an indoor air quality study / Siti Fatimah Ghazali, Suhaily Amran, Lailatul Akmar Mat Nor, Siti Nazrina Camalxaman and Maimunah Mustakim - Mat Nor, Lailatul Akmar; Camalxaman, Siti Nazrina; Mustakim, Maimunah (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2013)
Good indoor air quality promotes healthy indoor environment. Most of the indoor air contaminants originate from biological agents such as bacteria and fungi. Temperature and relative humidity are contributing factors to the growth of bacteria and fungi in indoor environment. The present study aims to (a) determine the concentration of airborne bacteria and fungi in old and new buildings and to compare these with the recommended maximum measurement, (b) correlate the microbial growth with temperature and relative humidity, (c) to identify various airborne bacteria and fungi in indoor environment. Microbial sampling was conducted using Standard Biostage Impactor. The building temperature and relative humidity were measured using Q-Track Plus Indoor Air Quality Meter. A total of 38 bacteria and 83 fungal genera were identified. Statistical analysis showed that the concentrations of total bacteria and fungi were below the maximum concentration as recommended by ICOP IAQ. There was also no correlation of relative humidity and temperature with the total concentrations of bacteria and fungi. The total concentration of bacteria and fungi also exhibited no significant difference between the old and new office buildings. The findings exhibited the presence of low levels of contaminant, thus indicating good air quality in the studied buildings.